2013
DOI: 10.1371/journal.pone.0075960
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Academic Stress Increases a Group of microRNAs in Peripheral Blood

Abstract: MicroRNAs (miRNAs) play key roles in regulation of cellular processes in response to changes in environment. In this study, we examined alterations in miRNA profiles in peripheral blood from 25 male medical students two months and two days before the National Examination for Medical Practitioners. Blood obtained one month after the examination were used as baseline controls. Levels of seven miRNAs (miR-16, -20b, -26b, -29a, -126, -144 and -144*) were significantly elevated during the pre-examination period in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…It is highly conserved and has multiple predicted targets in both humans and rats [44]. Many studies have demonstrated that miR-144 is involved in the response to mood stabilizer treatment [45], stress responses [46,47], and aging diseases [48]. Long-term treatment with the mood stabilizers lithium and valproate significantly up-regulates miR-144 expression in the rat hippocampus, which is one of the brain regions involved in mood regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly conserved and has multiple predicted targets in both humans and rats [44]. Many studies have demonstrated that miR-144 is involved in the response to mood stabilizer treatment [45], stress responses [46,47], and aging diseases [48]. Long-term treatment with the mood stabilizers lithium and valproate significantly up-regulates miR-144 expression in the rat hippocampus, which is one of the brain regions involved in mood regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cortisol, as a part of the glucocorticoid receptor (GR) complex, affects gene transcription and could, ultimately, permanently alter the offspring epigenome (Stahn et al, 2007). Intriguingly, recent evidence also suggests that microRNA, which could itself be regulated by cortisol and has been shown to be regulated by stress, may have a role in intergenerational inheritance (Cortez et al, 2011;Daxinger and Whitelaw, 2012;Honda et al, 2013;Issler and Chen, 2015).…”
Section: Biological Correlates In Offspringmentioning
confidence: 99%
“…Three of these studies used stressors of everyday life, such as academic exams or tests as events to be expected and therefore functioning as chronic psychological stressors [13,23,24]. …”
Section: Resultsmentioning
confidence: 99%
“…In 2012 [13] and 2013 [23], a group of scientists from the Department of Stress Science at the University of Tokushima, Japan, investigated alterations in miRNAs in the whole blood in conditions of chronic psychological stress. Katsuura et al [13] examined healthy fourth-grade medical students, taking a nationally administered examination for academic promotion.…”
Section: Resultsmentioning
confidence: 99%